(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this interview with Daniel Felipe Gomez, a member of Teatro Experimental de Cali, we talk about the group’s Collective Creation Method, one of the great contributions of TEC and Enrique Buenaventura to Latin American theater. The interview is part of a larger project, an attempt to seek an approximation to the group’s methodology, in order to disseminate it here in Brazil and minimize the bibliographic gap we have on the relevant theatrical and pedagogical work developed by the group.